An assessment of the harvesting and fuel performance of a single-pass cut-and-chip harvester in commercial-scale short-rotation poplar crops as influenced by crop and weather conditions. (June 2021) - Eisenbies, M.H.; Volk, T.A.; DeSouza, D.; Hallen, K.; Stanton, B.; Espinoza, J.; Himes, A.; Shuren, R.; Stonex, R.; Summers, B.; Zerpa, J.
Abstract: There is a need for data on commercial-scale harvesting operations in hybrid poplar short rotation crops to better understand costs and logistics, especially for modeling large scale biorefineries. An investigation was conducted on the in-field performance of a single-pass cut-and-chip harvester operating in commercial fields for over 370 individual wagon loads representing a range of crop and field conditions. Mean material capacity peaked at 70 Mg h −1 in dry conditions in lower biomass (<60 Mg ha −1 ), but was only 28 Mg h −1 during wet conditions and often higher standing biomass. Wet ground conditions require the harvester to divert additional power to maintaining forward movement, which results in decreased material capacity and increased fuel consumption. Crops with higher standing biomass had taller trees that do not always feed as smoothly into the harvester, slowing forward progress and lowering material capacity. Mean crop specific fuel consumption, L of fuel per Mg of biomass processed, generally decreased as standing biomass increased. When standing biomass was above 40 Mg ha −1 mean crop specific fuel consumption (FCC ) was 1.69 L Mg −1 in dry conditions and 3.98 L Mg −1 in wet conditions, but when standing biomass was below 40 Mg ha −1 FCC increased drastically (as high as 5 L Mg −1 ) because the harvester is putting more effort into forward speed instead of material processing. Developing relationships between material capacity and fuel consumption based on standing biomass and ground conditions at representative scales are essential for conducting environmental and economic analyses of these systems. Highlights: Harvester performance was assessed for 371 loads of short rotation poplar chips. Harvester throughput was influenced by standing biomass and field conditions. Throughput was >70 Mg h −1 in dry conditions, but <30 Mg h −1 in wet conditions. Crop specific fuel consumption generally varied 1–2 L Mg −1 in ideal conditions. These parameters are crucial for assessing poplar supply logistics and economics.